ORGANIZATIONAL TRANSFORMATION: WINNING COMPETITION IN BUSINESS - Shally Rizkiyanti; Fepi Leisthari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Whatever its shape and nature, organizational transformation will always be subject to change and will continue to evolve. The needs of the company where a someone works will impact their own needs, and vice versa. People and the organizations they work for are two sides of a coin that are inextricably linked and both require change. Poerwanto went on to say that corporations are currently dealing with the problem of constant worldwide change in a variety of spheres of existence. Organizations nowadays must prioritize being able to work more efficiently, quickly, and competitively. In the business world, competition is getting tougher day by day. To be able to compete, companies must be able to innovate and follow the latest trends. Business innovation is the main key in winning competition and remaining relevant in an ever- changing market. The main drivers of organizational transformation for the purpose of enhancing human resource capabilities are the competitiveness, globalization, market shifts, and ongoing technological advancements in corporate organizations. To gain a competitive advantage, organizations need to enhance their capabilities. This claim suggests that the foundation for enhancing the caliber of human resources in navigating change waves is transformation, also referred to as organizational change. This paper was written using a literature review methodology. The act of gathering, evaluating, and assembling data from dependable sources that is pertinent to the subject under discussion is known as a literature review. This research discusses the challenges of winning competition in business, strategies for winning competition in business, and the implications of internal transformation for winning competition in business.